(3QhVI GdCacGQ hGdCagGe deQJGO MGd GdCeGe hJYOGO ZRhGJ Phi GdGSdGes - (3GHf ZfGe , MSjf Hf ZfGe Hf CHj HcQ Hf ZfGe GdfLOj GdGMSGFj,J (B1225 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndag cd TF hbOQg JbOjQkG s
(3HgG fbU ai GdebOeIs
(3QJH GdeDda GdcJGH Ydi NeSI aUhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B328s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B146 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs